Analisis Performansi Protokol Routing Epidemic Dan Spray And Wait Pada DTN Berdasarkan Mobilitas Node - Jodi Prayoga Wahyudwi; Rakhmadhany Primananda; Achmad Basuki (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
DTN or Delay Tolerant Network is an internet network that does not matter the time delay. In this study, DTN routing analysis using Epidemic and Spray And Wait based on node mobility. In DTN routing use The One simulator application to list route path with actual city condition. In the performance appraisal, three test parameters were used: Probability of Submission, Overhead Ratio, Average Latency. In the first scenario, the highest Delivery Probability on the Open Shortest Path Mobility is 0.9853 messages, the second ranked Map by Movement of 0.9412 messages, and the last Route Movement Map of 0.9265 messages. In the second scenario, High Possibility on Mobility of Movement Based Map by 1 message, second rank of Open Shortest Path and Movement Map Map with the same value is 0.9796 message. On the third map of the highest Delivery Probability on Mobility Route Map Movement for 0.9457 messages, the second ranked Map Based Movement of 0.9225 messages, and last Open Shortest Path of 0.8837 messages. In Overhead Ratio, routing Epidemics in all mobility have. Average Lowest Latency on Open Shortest Path Mobility based on 72.9538 ms.